Biomass, Productivity and Nutrient Retention in Acacia catechu Willd. Plantations in Shiwalik Hills of Punjab Shiwalik Hills of Punjab - Rawat, Laxmi; Luna, R. K.; Kholiya, Deepak; Kamboj, S. K. (Indian Forester, 2008)
The biomass and nutrient distribution in Acacia catechu Willd. Plantations of Punjab has been studied at six sites of different ages (20, 22, 23, 24, 28, 32 years). The biomass ranged from 39.4 kg tree-1 to 738.98 kg tree-1 and from 77.29 to 223.46 t ha-1 in all these sites. Productivity ranged from 2.57 t ha-1 yr-1 (at 32 yrs) to 9.31 t ha -1 yr-1 (at 24 yrs). The contribution of individual tree components to total biomass varied as: leaf 1.41 to 4.29%; twig 2.92 to 6.31%, branch 10.95 to 19.98%, bark 6.65 to 10.69%, root 15.29 to 20.61% and bole 42.86 to 56.33%. The per cent contributions of all tree components in all the sites were in the order of bole > root > branch > bark > twig > leaf. Prediction models have been worked out by using allometric regressions. Among prediction variables tried D2H were found the most reliable parameters for prediction of biomass. In all these regressions, the biomass of the tree components has been taken as dependent variable and shows significant correlation coefficient confirming linear relationship The amount of various nutrients varies from N- 482.19 to 1041.04 kg ha-1, P- 30.32 to 92.72 kg ha-1, K- 194.81 to 767.05 kg ha-1, Ca - 523.3 to 1425.59 kg ha-1 and Mg - 27.27 to 80.13 kg ha-1, respectively. The percentage contribution of different nutrients to total nutrients are as; N (29.78 to 35.61%), P (1.61 to 2.76%), K (11.36 to 22.79%), Ca (38.64 to 54.86%) and Mg (2.01 to 2.61%), respectively. Nutrient losses through complete harvesting have been discussed and some suggestions have been given to replenish the nutrient loss and improve the site productivity.